EARNINGS QUALITY FROM A SHARIA ACCOUNTING PERSPECTIVE: TAX ALLOCATION, PROFIT PERSISTENCE AND PROFIT GROWTH - Amelia, Vinca; Martika Sari, Yetri; Dewi, Yulistia (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2025)
This research examines the influence of tax allocation, profit persistence and profit growth on profit quality partially and simultaneously in manufacturing companies listed on the Jakarta Islamic Index. The sampling technique used in this research was purposive sampling. The number of participants in this study was 55. The data analysis used is panel data regression using the E-Views 12 application. The results of this study show that partially the tax allocation variable (X1), earnings persistence (X2), and profit growth (X3) do not affect earnings quality (Y). Then, the research results show that simultaneously, tax allocation (X1), profit persistence (X2), and profit growth (X3) do not have a significant effect on profit quality. This research provides insight into managing manufacturing companies listed with JII to pay more attention to tax allocation, maintain profit stability, and ensure healthy profit growth. This is important to improve the quality of profits that can be trusted by investors and other stakeholders. Then, profits from a Sharia accounting perspective are allowed according to feasibility, fairness and impartiality principles and must not be infected by the influence of bias that should not occur.